Experience of creation and application of automatic meteorological stations in polar regions - Idrisov I.V.; Naumov A.V.; Kovchin I.S. (Российская Арктика)
The article deals with the development of automated technologies for observing the weather in the polar regions with the help of automatic autonomous meteorological stations. The experience of using the best domestic and foreign samples of this equipment is analyzed, ways of its improvement and development of the observation network are determined.